NURSES’ KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING INFECTION CONTROL MEASURES IN A PUBLIC CARE HOSPITAL: A CROSS-SECTIONAL SURVEY - Aziza Mayouf Alanzi¹, Muneera Lafi Ali Alharbi¹, Norah Hamoud Mohammed Alshammari¹, Hanaa Ashawi Ashban Alenazi¹, Amal Abdullah Bahl Alshammari¹, Amsha Mohammad Faraj Alsuhali¹, Madhawi Munawir Fawaz Aldahmashi¹ (Chelonian Research Foundation, 2022)
Background: Infection control is a crucial aspect of healthcare delivery, and nurses play a vital role in preventing healthcare-associated infections (HAIs). Assessing nurses' knowledge, attitudes, and practices (KAP) regarding infection control measures is essential for identifying gaps and implementing targeted interventions to improve patient safety. Objective: This study aimed to assess nurses' KAP regarding infection control measures in a public care hospital in Saudi Arabia and identify associated factors. Methods: A cross-sectional survey was conducted among 385 nurses working in a public care hospital in Riyadh, Saudi Arabia. A self-administered questionnaire was used to collect data on nurses' KAP regarding infection control measures. Descriptive statistics, independent t-tests, one-way ANOVA, and multiple linear regression were used for data analysis. Results: The overall mean scores for knowledge, attitudes, and practices were 78.5%, 82.3%, and 75.6%, respectively. Significant differences in KAP scores were found based on age, educational level, years of experience, and attendance of infection control training (p < 0.05). Multiple linear regression revealed that higher educational level, longer years of experience, and attendance of infection control training were significant predictors of better KAP scores (p < 0.05). Conclusion: Nurses in this study demonstrated good knowledge, positive attitudes, and adequate practices regarding infection control measures. However, there is still room for improvement, particularly in infection control practices. Targeted educational interventions and regular training programs are recommended to enhance nurses' KAP and reduce the risk of HAIs. Keywords: infection control, knowledge, attitudes, practices, nurses, cross-sectional study